(untitled) (Revista Brasileira Multidisciplinar, 2022)
This study aimed to evaluate the perception of the multiprofessional health team in a university hospital in relation to the reconciliation of medications. This research was observational, descriptive and qualitative, being carried out at the University Hospital Mário Araújo, linked to the University Center of the Campanha Region-URCAMP (Bagé-RS). The hospital’s health professionals were coded with the first letter of the profession followed by numerical order, as an example: doctors (M1, M2) and so on. Guiding questions were launched through semi-structured interviews, with recording and recording of the interviewees’ speech, for later analysis of Bardin’s content. It was possible to study the variables referring to the knowledge of the multidisciplinary team on medication reconciliation; evaluation of the practice of medication reconciliations in the hospital context; moment when the practice of reconciling medicines becomes more important; perception of the multidisciplinary team in relation to pharmaceutical services and assessment of the pharmacist’s perception of the process of implementing the drug reconciliation service. Of the 21 professionals interviewed, it was possible to include 15 interviews in the study, in which, after analyzing the responses, the following categories emerged: “understanding about medication reconciliation”, “the practice of reconciling medications” and “multidisciplinary team vision”. It was observed that the implementation of drug reconciliations in the hospital under study advanced in front of other realities and is a practice that requires constant training of the team for patient safety. It was noticed that the pharmacist has been recognized by the health team and gaining space for the exercise of his clinical functions. It was observed that the implementation of drug reconciliations in the hospital under study has advanced in the face of other realities and is a practice that requires constant training of the team for patient safety. It was noticed that the pharmacist has been recognized by the health team that has been gaining space for the exercise of its clinical functions.